COMPARISON STUDY BETWEEN SIMPLE LAWSUITS IN SMALL CLAIM COURT AND USUAL CLAIMS - Ridwan Pratama (Indonesia Private Law Review, 2023)
Settlement of disputes through the courts is not the right choice if the loss is small because what is demanded is not worth what is incurred. Then the Supreme Court issued Perma Number 2 of 2015, amended by Perma 4 of 2019, concerning simple lawsuits. The birth of the Perma has the consequence of a settlement through an ordinary civil lawsuit and a simple lawsuit. Based on this, the authors examine the differences and similarities in settling ordinary civil lawsuits with simple lawsuits and the constraints of both. This research uses a normative-empirical legal method with a descriptive research type with a statutory approach. The data used are primary and secondary data, consisting of primary legal materials, secondary, and tertiary, then data analysis was carried out qualitatively and comparatively. The study results show that: First, the equation of a simple lawsuit and an ordinary lawsuit is to accommodate the classification of lawsuits against the law and default, applying the actor sequitur forum rei principle, there are verses legal remedies, and others. While the difference between a simple lawsuit and an ordinary lawsuit is that in a simple lawsuit, there are various restrictions, such as the value of a material claim is a maximum of IDR 500,000,000.00 and is not resolved through a special court or dispute over land rights, only one party each, the Principal must be present in person at every trial, in ordinary civil lawsuits there are no such restrictions, and so on. Second, there are obstacles to resolving ordinary civil lawsuits, such as a long time, no restrictions on cases that can be appealed, and various obstacles hamper the implementation of decisions. While the obstacles to resolving a simple lawsuit are that the Principal must attend in person at every trial, filing an objection by the Plaintiff nullifies the Defendant's right to file verzet and implement a decision that has not been specifically regulated.